Students' Metacognitive Strategies in Facing Learning Difficulties in Serenity & Kurtosis Materials - Tandungan, Junadelvia (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the metacognitive strategies used by students in overcoming learning difficulties in statistical materials, especially the concepts of skewness and kurtosis. This material is often considered complex because it requires an understanding of abstract mathematical concepts and the ability to interpret statistical data. The research uses a qualitative approach with a case study method on students of the mathematics education study program. Data collection techniques were carried out through in-depth interviews, participatory observations, and document analysis. The results of the study showed that students used various metacognitive strategies such as learning planning, comprehension monitoring, and self-evaluation and reflection after the learning process. This strategy has been proven to help students identify misconceptions, strengthen their understanding of concepts, and improve their problem-solving skills in solving statistical problems. These findings provide important implications for the development of learning models that support students' metacognitive awareness in understanding complex statistical material.